A malaria merozoite surface protein (MSP1)-structure, processing and function - Anthony A. Holder; Michael J. Blackman; Petra A. Burghaus; Jonathan A. Chappel; Irene T. Ling; Neil McCallum-Deighton; Shafrira Shai (Memorias do Instituto Oswaldo Cruz, 1992)
Merozoite surface protein-1 (MSP-1, also referred to as P195, PMMSA or MSA 1) is one of the most studied of all malaria proteins. The proteins. The protein is found in all malaria species investigated and structural studies on the gene indicate that parts of the molecule are well-conserved. Studies on Plasmodium falciparum have shown that the protein is in a processed form on the merozoite surface, a result of proteolytic cleavage of the large percursor molecule. Recent studies have identified some of these cleavage sites. During invasion of the new red cell most of the MSP1 molecule is shed from the parasite surface except for a small C-terminal fragment which can be detected in ring stages. Analysis of the structure of this fragment suggests that it contains two growth factor-like domains that may have a functional role.